(untitled) (Annals of Medical Research, 2021)
Aim: Patients with acute coronary syndrome who underwent percutaneous coronary intervention (PCI) constitute the group with the highest risk of contrast-induced nephropathy development. Contrast media exposure might increase in patients who have lesions with >70% stenosis in the major epicardial arteries. Also, the impaired kidney function is associated with severity of coronary artery disease. We evaluated the relationship with severity of coronary artery disease (CAD) calculated by Gensini score and contrast induced nephropathy (CIN) in patients with mild renal insufficiency in acute coronary syndrome (ACS). Material and Methods: We enrolled 227 patients with ACS who underwent percutaneous coronary intervention. Patients were divided into groups according to CIN development. Severity of CAD was evaluated by Gensini score. Logistic regression analysis (univariate and multivariate) was performed to evaluate the predictors of CIN using variables that are clinically related to CIN. The 95% confidence interval (CI) and odds ratios (OR) were presented. Receiver–operating characteristic (ROC) curve was performed to demonstrate the sensitivity and specificity of the Gensini score.Results: A total of 69 (30.1%) patients with ACS had CIN. Compared to CIN (-) patients, CIN (+) patients had higher Gensini score, incidence of diabetes mellitus and amount of contrast media. Multivariate logistic regression analyses demonstrated that Gensini score, DM and amount of contrast media were independent risk factors for CIN development (p 0.05 for all parameters).Conclusion: Gensini score, which simply shows severity of CAD, may be helpful in the determination of CIN risk in patients with ACS.